The Reporting of the Journalists of "Raz, Dwa, Trzy" at the Olympic Games in Berlin in 1936 - Miłosz Stępiński (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
The Olympic Games of 1936 in Berlin found sports and Olympic movement in the Second Republic of Poland at astage of developing and strengthening its organizational structure. The most famous and honored sport newspapers were: “Przegląd Sportowy” from Warsaw and – published by “IKC” concern from Cracow – “Raz, Dwa, Trzy”. The circulation of both titles constituted more than 3/4 of the circulation of all the sporting titles in the Second Republic of Poland. In this paper reports of “Raz, Dwa, Trzy” correspondents of the Olympic Games and the capital of Germany were presented. The analysis of the reporting of the journalists of “Raz, Dwa, Trzy” from the The Games of the XI Olympiad in Berlin allows to conclude that the narration of the reports fully corresponded with the aforementioned Polish-German Press Agreement of the 7th October 1934 and its basic assumptions. At the same time it was in accordance with the appreciation expressed to German organizers by foreign correspondents. The relations of the correspondents from Cracow indicate that Hitler’s’ regimentation reached its goals also in this environment. Enormous sports and infrastructural investments in the Third Reich, together with incorporating the modern technology, high degree of social discipline and the penchant for order and cleanliness, so typical for Germans, found their expressive reflection in the pages of “Raz, Dwa, Trzy”.